Cardiovascular Disease and Hemodialysis (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
Cardiovascular disease is the leading cause of morbidity and mortality in patients undergoing chronic dialysis treatments. The persistently elevated mortality rates in this population reflect not only the complexity of cardiovascular disease pathogenesis in uremia but also the inadequacy of current preventive and therapeutic strategies. Beyond the clinical implications, this burden carries significant economic consequences for healthcare systems. These unique pathogenic mechanisms demand focused research efforts and tailored interventions to improve outcomes in this vulnerable population. “Cardiovascular Disease and Hemodialysis” brings together original clinical research that deepens our understanding of the multifaceted cardiovascular burden in this population. The selected studies provide important insights into risk stratification, predictive biomarkers, treatment outcomes, and the pathophysiology of CVD in HD patients.